Age characteristics in buli tumor patients at the General Hospital For The Jayapura Regional period 2017-2022 - Wonatorey, Nickanor Kaladius Reumi; Korwa, Stenley Christian (Goodwood Publishing, 2025)
Purpose: Buli-buli tumors, also known as vesica urinaria (bladder) tumors, represent the second most common malignancy after prostate cancer and are found twice as often in men than in women. The most frequent clinical symptoms include painless hematuria and urinary tract complaints, such as frequency, urgency, and dysuria. According to the Global Cancer Incidence, Mortality, and Prevalence (GLOBOCAN) 2020 data, there were 573,000 cases of bladder tumors worldwide, accounting for approximately 3% of all new tumors. This study aims to identify and describe the epidemiological characteristics of patients with buli-buli tumors treated at Jayapura Hospital. Research Methodology: This research used a descriptive method by analyzing secondary data from the medical records of patients diagnosed with buli-buli tumors at Jayapura Hospital between 2017 and 2022. Results: The findings revealed 61 buli-buli tumors. The largest proportion was in patients aged >50 years (30 cases, 49.2%). The second largest group was 41–50 years with 24 cases (39.3%), followed by 31–40 years with five cases (8.2%), 20–30 years with one case (1.6%), and <20 years with one case (1.6%). Conclusions: Bladder tumors at Jayapura Hospital are most frequently found in patients over 50 years of age, suggesting that increasing age is an important risk factor. Limitations: This study is limited to retrospective secondary data from one hospital and may not fully represent the prevalence patterns in Papua or Indonesia as a whole. Contribution: This study provides initial epidemiological evidence of bladder tumor cases in Jayapura, serving as a reference for health authorities, future research, and the development of strategies for early detection and prevention in Eastern Indonesia.